Discussion, Part II: Psychoanalytic Reflections on the Impact of Separation and Divorce: High-Conflict Parents and Their Children: The Inside Story. Issue 1 (1st January 2019) - Straus, Robert B.
ABSTRACT: In Part II of his discussion, Straus turns his attention to high- and very high-conflict separation and divorce cases. He points out that it would be extremely difficult for these parents to emotionally support an analytic treatment for their child. He gives the inside story of how these parents, once at least "good enough, " can now barely parent at all, and describes the evolution of their personal destruction and harm to their children. He speaks to what the childhood experience now becomes for the child of high-conflict parents. Straus also illustrates with personal examples the raw feelings, such as anger and hate, that get stimulated for the professional who engages with these families in this very challenging and heart-wrenching work.